2016
DOI: 10.1128/cvi.00654-15
|View full text |Cite
|
Sign up to set email alerts
|

Poor Correlation between Pneumococcal IgG and IgM Titers and Opsonophagocytic Activity in Vaccinated Patients with Multiple Myeloma and Waldenstrom's Macroglobulinemia

Abstract: e Patients with multiple myeloma and other B cell disorders respond poorly to pneumococcal vaccination. Vaccine responsiveness is commonly determined by measuring pneumococcal serotype-specific antibodies by enzyme-linked immunosorbent assay (ELISA), by a functional opsonophagocytosis assay (OPA), or by both assays. We compared the two methods in vaccinated elderly patients with multiple myeloma, Waldenstrom's macroglobulinemia, and monoclonal gammopathy of undetermined significance (MGUS). Postvaccination ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…These nonfunctional antibodies may be able to bind to polysaccharide coated on a plate and thus be positive on ELISA, but are not able to opsonize whole bacteria [28] . Interestingly, a recent paper found a good correlation between ELISA and OPA after pneumococcal vaccine in MGUS but not in MM patients [24] . In our hands as in MGUS patients, we found a good correlation between ELISA and OPA in SMM patients (supplementary data), except for baseline with only 2 serotypes (14 and 18C) on the seven tested which had good correlations between the two tests ( Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These nonfunctional antibodies may be able to bind to polysaccharide coated on a plate and thus be positive on ELISA, but are not able to opsonize whole bacteria [28] . Interestingly, a recent paper found a good correlation between ELISA and OPA after pneumococcal vaccine in MGUS but not in MM patients [24] . In our hands as in MGUS patients, we found a good correlation between ELISA and OPA in SMM patients (supplementary data), except for baseline with only 2 serotypes (14 and 18C) on the seven tested which had good correlations between the two tests ( Fig.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, this study is the first to evaluate the immunogenicity of pneumococcal vaccination in SMM patients. Pneumococcal vaccines have been evaluated in MGUS and in MM patients [ 24 , 25 ]. However, SMM patients differ from MM patients as they have no evidence of end-organ damage and/or other myeloma-defining events.…”
Section: Discussionmentioning
confidence: 99%
“…Criteria and guidelines for Ig replacement vary internationally . For example, British, but not Australian, criteria require a trial of prophylactic antibiotics and pneumococcal vaccination before Ig replacement, although no randomised trials prospectively assessing this strategy have been reported, and vaccine responses are impaired in secondary hypogammaglobulinaemia …”
Section: Introductionmentioning
confidence: 99%
“…8 Consistent with our pilot findings, Karlsson and colleagues showed that total IgG antibody response does not correlate with functional assays of pneumococcal killing. 5 Thus, from this limited data, it appears that clinicians should not rely on quantitation of IgGs nor their subclasses when deciding whether or not to vaccinate patients with MM. Circles -Controls Diamonds -Patients Our study has several limitations, for example, small sample size, sample dropouts and a heterogeneous subject population.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody response of a doubling in immunoglobulin G (IgG) and immunoglobulin M antibody titers has been historically used as a metric of response, but in general this has not been clinically validated. 5 Many clinicians may not comply with recommendations for pneumococcal pneumonia vaccination (PV) because of a perception that MM and other cancers of the immune system inherently are accompanied by immunologic compromise, especially in the setting of reduced IgG levels. We hypothesized that total IgG levels and levels of IgG subclasses might predict responsiveness to PV.…”
mentioning
confidence: 99%